Naples in the time of cholera, 1884-1911 - Snowden, Frank M. (Frank Martin), 1946- (Cambridge University Press, 1995)
This 1995 book is a medical and social history of Italy's largest city during the cholera epidemics of 1884 and 1910-11. It explores the factors that exposed Naples to risk; it examines such popular responses as social hysteria, riots and religiosity; and it traces therapeutic strategies. Cholera also became a metaphor for discontent with the regime: the 1884 outbreak was a national issue which led to the rebuilding of the city amidst widespread corruption. The book sets Naples in a comparative international framework; the disease is also related to larger historical issues, such as the nature of liberal statecraft, the 'Southern Question', mass emigration, organised crime, urban renewal, and the medical profession.